Human–Animal Interaction and Older Adults: An Overview - Gee, Nancy R.; Mueller, Megan K.; Curl, Angela L. (Frontiers in Psychology, 2017)
Both pet ownership and animal-assisted therapy are becoming increasingly popular in the United States, and the science of human-animal interaction (HAI) seeks to explore how these relationships with animals can impact health and well-being. In particular, one burgeoning area of research is the role of HAI in healthy aging, given the potential for HAI as an important feature of health and well-being in older adults. The purpose of this review is to summarize and evaluate existing research in this innovative area of scholarship, identifying the potential benefits and risks of both pet ownership and animals in therapeutic settings for older adults. We will also identify recommendations for future research and applications in this developing area of scholarship.